2017
DOI: 10.1186/s12943-017-0646-3
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of lipid metabolism in cancer metastasis

Abstract: Cancer cells frequently display fundamentally altered cellular metabolism, which provides the biochemical foundation and directly contributes to tumorigenicity and malignancy. Rewiring of metabolic programmes, such as aerobic glycolysis and increased glutamine metabolism, are crucial for cancer cells to shed from a primary tumor, overcome the nutrient and energy deficit, and eventually survive and form metastases. However, the role of lipid metabolism that confers the aggressive properties of malignant cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
377
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 497 publications
(412 citation statements)
references
References 109 publications
11
377
0
Order By: Relevance
“…Currently, the pivotal role of FA metabolism in cancer metastasis has been highlighted [26], and lncRNAs have been demonstrated to regulate FA metabolism via different mechanisms [27]. Therefore, we further examined whether LNMICC was linked to altered FA metabolism in cervical cancer.…”
Section: Lnmicc Activates Fatty Acid Metabolism In Cervical Cancer Cementioning
confidence: 98%
“…Currently, the pivotal role of FA metabolism in cancer metastasis has been highlighted [26], and lncRNAs have been demonstrated to regulate FA metabolism via different mechanisms [27]. Therefore, we further examined whether LNMICC was linked to altered FA metabolism in cervical cancer.…”
Section: Lnmicc Activates Fatty Acid Metabolism In Cervical Cancer Cementioning
confidence: 98%
“…However, one of the key pathological manifestations of PE is a restricted invasion of trophoblast cells [6][7][8]. The rapid growth of tumor cells depends on a sustained energy supply, as highlighted by Luo et al's demonstration of the role of lipid metabolism in tumor invasion [9]; the impairment of trophoblasts invasion in PE placenta may thus be consequent on a compromised energy supply. Pertinently, Yan et al reported that fatty acid binding protein (FABP) expression was increased in placentas from women with PE and that silencing FABP decreased trophoblasts proliferation, migration and invasion [10].…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is greatly aided by an enhanced dependence on glutamine metabolism, which facilitates enhanced lipid synthesis (needed for the formation of LEVs) through GLS, glutamate dehydrogenase (GDH), reductive carboxylation of α‐ketoglutarate (α‐KG) through isocitrate dehydrogenase (IDH), citrate lyase and finally FASN as shown in Figure . This paradigm integrates the role of enhanced glutamine metabolism, enhanced lipid synthesis and lipid metabolism in the establishment of organ specific metastases …”
Section: Discussionmentioning
confidence: 99%